Effects of land use and riparian flowpath on delivery of dissolved organic carbon to streams - Stuart Findlay; John M. Quinn; Christopher W. Hickey; Greg Burrell; Malcolm Downes (Limnology and Oceanography, 2001)
A set of near‐stream flowpaths in pasture, native forest and exotic pine plantations in New Zealand was sampled to describe differences in dissolved organic carbon (DOC). The quantity and bioavailability of DOC varied among flowpaths in different land uses, with higher concentrations of DOC in near‐stream flow paths than the parent groundwater emerging from the hillslope. Tiles incubated in these waters did not consistently yield higher bacterial growth rates than tiles incubated in groundwaters. DOC composition, measured as fluorescence and absorbance properties and extracellular enzyme fingerprints, differed significantly among land uses and position along flowpath. Differences in riparian vegetation can indirectly affect DOC by altering exposure to ultraviolet radiation. A 2‐h exposure of water from subsurface flowpaths to full sunlight caused marked changes in fluorescence characteristics of water from the pasture catchment but only small changes in water from the native forest catchment. There were up to fivefold differences in extracellular enzyme activities on tiles incubated in light‐exposed water for the native forest site, but not for the pasture site. Bacterial growth and respiration were higher on tiles incubated in native forest water exposed to sunlight, but there was no light effect on growth for tiles incubated in water from the pasture flowpath. These results indicate that riparian flowpaths will affect the quantity and character of DOC delivered to streams and ultraviolet exposure may, at least in some cases, alter DOC bioavailability.

Land‐use effects on the hyporheic ecology of five small streams near Hamilton, New Zealand - Andrew J. Boulton; Mike R. Scarsbrook; John M. Quinn; Greg P. Burrell (New Zealand Journal of Marine and Freshwater Research, 1997)
Although the importance of the subsurface saturated interstitial zone (hyporheic zone) to the ecological functioning and maintenance of water quality of stream ecosystems is well known, there is little information on the impacts of different forms of land use upon this zone. Hyporheic physico‐chemistry and invertebrates were compared among small streams draining hill‐country catchments under pasture, exotic pine forest, and native forest near Hamilton, New Zealand. In streams draining native forest, the hyporheic zone harboured a relatively diverse invertebrate fauna comprising mostly taxa common in the surface benthos, although a few apparently obligate hyporheic taxa (ostracods, blind amphipods) were collected. Few individuals and taxa occupied the hyporheic zones of streams draining pasture with some groups such as water mites conspicuously absent. The hyporheos of the stream in exotic pine forest was similar in richness and abundance to that of the pasture streams. Hyporheic water temperatures were significantly higher in the pasture streams than those in pine or native forest. There were strong positive correlations between percentage saturation of dissolved oxygen in the hyporheic zones of all streams and both species richness and total invertebrate abundance. We suggest that land clearance for pasture leads to hill slumping and siltation that bury the lateral bars along the stream channels, rendering this habitat unsuitable for hyporheic invertebrates. Channel narrowing and incision may physically remove further hyporheic habitat, and the reduction of flushing flows to remove interstitial silt and clay leads to low hyporheic dissolved oxygen concentrations and reduced colonisation by surface benthos.